2003
DOI: 10.1177/0886109903251405
|View full text |Cite
|
Sign up to set email alerts
|

African American Women at Midlife: the Relationship Between Spirituality and Life Satisfaction

Abstract: In order to examine the potential relationship between life satisfaction, spirituality and other demographic variables, 147 African American women from Alabama, Florida, Georgia, Kentucky, Michigan and Missouri were asked to complete the Adult Life Satisfaction Scale (ALSS) and the Black Women=s Spirituality/Religiosity Measure (BWSRM). In-depth interviews were also conducted with six African American women. Data obtained were subjected to correlated groups t test, Pearson r=s and regression analysis; content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…[14]. In Starks and Hughey's study it was found that spirituality plays a role in life satisfaction in middle-aged African women, regardless of age, income and education [15]. Brillhart's research on relationships between spirituality, and life satisfaction on people with spinal cord injury showed a significant positive correlation between life satisfaction and psychological factors [16].…”
mentioning
confidence: 99%
“…[14]. In Starks and Hughey's study it was found that spirituality plays a role in life satisfaction in middle-aged African women, regardless of age, income and education [15]. Brillhart's research on relationships between spirituality, and life satisfaction on people with spinal cord injury showed a significant positive correlation between life satisfaction and psychological factors [16].…”
mentioning
confidence: 99%